Análise morfológica facial com finalidade forense: estudo da população brasileira - Falcão, Tainá Nascimento (2022)
The wide use of video surveillance systems in public and private spaces has allowed the recording of the most diverse criminal offenses. Thus, often, the identity of the people involved needs to be extracted from this material and therefore, the analysis of facial features is fundamental for the identification. The high variability of the face, mainly related to the ancestral group to which it belongs, makes it difficult to develop a universal instrument for facial morphological analysis. The present study aimed to propose morphological classification categories for the face and its anatomical structures. These structures were illustrated in order to support the elaboration of an atlas that favors the morphological analysis of the face of Brazilians in the forensic practice. This was a descriptive study, with analysis of the frequency and distribution of 13 photoanthropometric facial ratios (RFAs) through quantitative tests on an existing database. RFAs referring to: height and width of the face, width of the eye, intercantal distance, length and width of the nose, height and width of the philtral crest, thickness and width of the mouth, thickness of the upper and lower lips and height of the chin were analyzed, in a sample of 5,000 individuals aged between 18 and 22 years, equally distributed between the sexes. For the RFAs that had a normal distribution, mean data and ±1.5 SD were used in order to categorize facial measurements into regular, below or above average. Non-parametric RFAs were analyzed using median data and 10 and 90 percentiles. Based on the average iris diameter, already consolidated as the most stable measure of the face, the RFA values were converted to a numerical scale in centimeters, allowing the illustration of female and male faces. Thus, it was possible to categorize the facial anatomical structures and, consequently, to visualize the facial morphological pattern of the young adult Brazilian population.